Primary erythromelalgia mainly manifested by hypertensive crisis: A case report and literature review - Feng, Shuo; He, Zhanwen; Que, Liping; Luo, Xiangyang; Liang, Liyang; Li, Dongfang; Qin, Lijun (Frontiers in Pediatrics, 2022)
Background: primary erythrocytic (PEM) is a rare autosomal dominant single gene disease. Most of the changes of gene loci can be found by whole exon gene sequencing, and the clinical symptoms and patient survival can be improved by specific site-to-site drug treatment. The other manifestations of this patient population are not remarkable. After the application of common drugs, the toxicity and side effects can be limiting. In addition to other common clinical manifestations, we found that the only unique manifestation of this patient was hypertensive crisis. Following multidisciplinary diagnosis and treatment (MDT), we decided to first control hypertension to alleviate the acute and critical patients. However, after controlling the hypertensive crisis, we unexpectedly found that the clinical symptoms of the patients had been significantly improved. Therefore, we concluded that the use of antihypertensive drugs can treat erythematous limb pain with the clinical manifestation of hypertensive crisis. Here, we describe a typical PEM disease, primary clinical features, diagnosis and treatment.